Spying for the people Mao's secret agents, 1949 - 1967 - Schoenhals, Michael (Cambridge Univ. Press, 2013)
"In this fascinating account, Michael Schoenhals tells the story of the domestic covert operations of Mao's public security organs through a detailed examination of the cultivation and recruitment of their agents, their training, and their operational activities"-- Provided by publisher
Includes bibliographical references and index
Machine generated contents note: Bone of Contention -- Missing Dimension -- 1.Public Security: The Institutional Framework -- A Central Party Ministry -- Soviet Expertise: Unwelcome Guidance -- A Tale of Two Ministers -- The CMPS 1st Bureau: Preempting Subversion -- Directors of Operations: Primus Inter Pares -- The CMPS 2nd Bureau: Preventing Sabotage -- Economic Protection: "We're All Amateurs at This!" -- Cooperation: An Elusive Goal -- 2.Agents by Category: Informers, Enablers, and Guardians -- "Is It Moral, Then? It Is Highly Moral" -- Secret Investigation Agents -- "Building Up Resources Over Time": Operating in Ethnic Minority Regions -- Case Agents -- Critical Asset Guardians -- Restrictions on Where to Run Agents -- 3.The Recruitment Base: Where Utility Trumps Class -- Identifying the Recruitment Base -- The Bad Guys -- The Backward Gray Masses -- The CCP's Activist Constituency -- Gender Matters: No Sex Please, We're Chinese! --
Contents note continued: 4.Finding the Right Person for the Job: Operational Profiling -- Rationale and Purposeful Engagement -- Nerves and Discretion: Qualities of a Good Agent -- A Question of Trust -- Exploiting Archives -- A Visit to the Grass Roots -- Tapping Additional Sources -- 5.Recruitment -- Preparation Is Key -- The Recruitment Interview -- The Power Ladder -- The Patriotic Pitch: Your Country Needs You! -- The Gradual Pitch: I Thought You'd Never Ask -- The Hard Pitch: An Offer You Can't Refuse -- The Agent's Personal File -- When Recruitment Fails -- 6.Training and Tradecraft: Behind the Covert Front -- Training in the Academy -- Textbooks and Extracurricular Reading Matter -- Learning on the Job -- Keeping Clandestine Premises -- Using Secret Rendezvous Premises -- Coded Conversations -- Secret Writing -- Gadgets and Gizmos: Covert Technologies -- Corruption and Complaints -- 7.Agent Running: Beijing Rules -- Direction -- Agent Briefing -- Agent Debriefing --
Contents note continued: Covert Information and the Courts -- Control -- Agent Rewards and Welfare -- Orderly Termination
Keywords: Geschichte 1900-2000; Geschichte 1949-1967; Intelligence service / China / History / 20th century; Secret service / China / History / 20th century; Spies / China / History / 20th century; Domestic intelligence / China / History / 20th century; Internal security / China / History / 20th century; Geschichte; Innere Sicherheit; Polizeistaat; Spitzel; China